Energy absorption of shape memory structures - Yong, Wei Hong (2012)
This project looks at the energy absorption ability of a Nickel-Titanium Shape Memory Alloy in the form of a circular thin-wall tube. Cyclic compression tests were conducted on the Ni-Ti specimen, where the specimen strain is incremented after every complete cycle of loading and unloading. The energy absorption of the specimen was determined by measuring the Force and Displacements parameters of the specimen in the form of Force Vs Displacement graphs. The energy absorbed was determined from the area under the curve of these graphs. The Ni-Ti specimen in the as-received state is in the Austenite phase at room temperature. This was verified by Differential Scanning Calorimetry tests that were conducted on the specimen. Axial compression and Lateral compression of the Ni-Ti specimen were conducted using different arrangements of the Ni-Ti specimen. A total of 6 sets of compression test were conducted and the energy absorption abilities of the Ni-Ti specimen were compared to see which form of loading gives better energy absorption. The results show that for all 3 sets of arrangements tested, axial loading gives better energy absorption capabilities as compared to lateral loading. The specimens under axial loading were able to undergo a full recovery upon unloading for all 3 sets of arrangement with little or almost negligible residual strain. This is in contrast with the specimens under lateral loading, where they were unable to obtain a full recovery upon unloading for all 3 sets of arrangement, and they leave behind significant residual strain or failure of the specimen itself.